A comparison of match load between padel and singles and doubles tennis - Armstrong, C.; Reid, M.; Beale, C.; Girard, O. (International Journal of Sports Physiology and Performance, 2023)
While tennis remains a popular activity worldwide, emerging racket sport formats such as padel are currently undergoing unprecedented growth. Padel is one of the most practiced sports in South America and Spain and is now expanding rapidly across Europe and other continents.1 Although sharing many similarities with tennis (ie, intermittent multidirectional nature of the game, rules and scoring system), playing surfaces, court dimensions, net height, and equipment used differ from those of tennis in padel. To illustrate, padel is always practiced in pairs on an enclosed court (ie, delimited by glass and gratings the ball bounces off) ~25% smaller than the size of a tennis court. These idiosyncrasies suggest that the game demands imposed on players may differ between racket sport formats.